POLITICAL COMMUNICATION DURING THE 2014 PRESIDENTIAL CAMPAIGN: ONLINE MEDIA COVERAGE - Cristina Cîrtiţă-Buzoianu (Studies and Scientific Researches: Economics Edition, 2015)
The election campaign has lately become a real challenge where all the political actors display their skills, the communication ones, but also those related to the electoral marketing and public relations which play a vital role in creating the image of a particular candidate. The interest that the public manifest towards the presidential debates, as well as towards all the means of political communication used by the actors involved represents a reference point in the construction of an election campaign. Our paper aims to achieve a quantitative analysis of the communicational messages sent during the 2014 presidential campaign in the online media. In this respect, we are going to conduct a media monitoring on two central newspapers, namely “Evenimentul Zilei” (“Daily Event”) and “Jurnalul Național” (“National Journal”), to track the online media visibility of the political communication starting from several indicators predefined in order to measure the efficiency of the political communication. Thus, our approach considers the influence of political communication in the election campaign as it appears in the online press in Romania.